Ocular Tumors in Animals and Humans. - Peiffer, Robert L. (John Wiley & Sons, 2008)
The application of evidence-based veterinary medicine (EBVM) can assist in improving and optimising the diagnosis, prognosis, control, treatment and ultimately the welfare of animals. It can also provide the user with a methodology for appropriate, patien.